Numerical simulation and application of nanomagnetic enzyme in a liquid-solid magnetic fluidized bed. (December 2018) - Yu, Dianyu; Wang, Yuqi; Yu, Bohan; Wang, Tong; Zhang, Ruchun; Jiang, Lianzhou; Wang, Liqi; Elfalleh, Walid
Graphical abstract: Highlights: Free phospholipase A1 was immobilized on magnetic Fe3 O4 /SiOx-g-P(GMA) nanoparticles. The motion law of nanomagnetic enzyme particles in fluidized bed was simulated. Using optimal numerical simulation, soybean oil was degummed in a multistage process. The optimized conditions improved significantly the enzymolysis reaction. Abstract: Compared to traditional methods, the enzymatic degumming shows the advantages of a clear reaction substrate, mild reaction conditions, low energy consumption and reduced environmental pollution. Free phospholipase A1 (PLA1 ) was immobilized on magnetic Fe3 O4 /SiOx-g-P (GMA) nanoparticles to obtain a nanomagnetic immobilized PLA1 with a particle size of 100.50 ± 1.3 nm and an activity of 2150 ± 25 U/g. The Eulerian-Lagrangian model with particles as discrete phase and liquid as continuous phase was selected. The motion law of nanomagnetic enzyme particles in liquid-solid magnetic fluidized bed was simulated. Under the conditions of a magnetic field intensity of 0.022 T and a flow rate of soybean crude oil of 0.0025 m/s, the distribution status of nanomagnetic enzyme in the magnetic fluidized enhanced the enzymolysis reaction. Using the main parameters obtained by numerical simulation, soybean crude oil was degummed in a multistage magnetic fluidized bed. Under the conditions of a magnetic enzyme dosage of 0.10 g/kg, a reaction temperature of 63 °C and a reaction system pH of 6.3, after 6.0 h of reaction, the residual phosphorus contents in the oil was 8.2 mg/kg, and the relative activity of the nanomagnetic enzyme was still 86%. The optimized conditions improved significantly the efficiency and stability of the enzymolysis reaction of nanomagnetic enzyme.